Implementasi Model Pembelajaran Kooperatif Tipe Think Pair Share (TPS) dengan Pendekatan Saintifik Terhadap Hasil Belajar Siswa - Hayu Restiani; Euis Mawaddah Sariniwati (Integrated Science Education Journal, 2022)
Purpose of the study: This study aims to determine whether there is a significant effect on the application of the Think Pair Share (TPS) cooperative learning model with a scientific approach to the learning outcomes of seventh grade students of SMP Negeri 10 Jambi City. Methodology: This type of research is an experimental research with a quantitative approach. The research design used was a posttest-only control design with two sample classes. The experimental class was taught using the TPS model in order to see its effect on student learning outcomes. The data collection method used test questions and observation sheets. Main Findings: Because tcount > ttable, H1 is accepted and H0 is rejected at the 95% confidence level, so it can be concluded that there are differences in student learning outcomes using the Think Pair Share (TPS) cooperative learning model and learning using direct learning models in class VII SMP State 10 Jambi City. Novelty/Originality of this study: Based on the results of the study, it can be concluded that there is a significant effect between the application of the Think Pair Share (TPS) cooperative learning model with a scientific approach on the learning outcomes of Class VII students of SMP Negeri 10 Jambi City.